A prospective observational study on loop diuretic utilization in a tertiary care hospital setting - Nayak, Hemant; Bhat, Waseem Hussain; Prabhudev, B. R.; Ramaiah, Balakeshwa (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Loop diuretics are essential for managing fluid overload in conditions like heart failure and chronic kidney disease. However, data on their utilization and adverse outcomes in resource-limited settings are scarce. To evaluate utilization patterns, adverse drug reactions (ADRs), and outcomes of loop diuretic therapy in a tertiary care hospital. Methods: A prospective observational study was conducted on 100 inpatients from January 2023 to October 2023. Data on demographics, clinical indications, ADRs, and prescription patterns were analyzed. Results: Furosemide was most prescribed (70%), followed by torsemide (20%) and bumetanide (10%). Main indications included congestive heart failure (40%), hypertension (24%), and chronic kidney disease (20%). Common ADRs were hypokalemia (16%), hypotension (10%), and dehydration (6%). Symptomatic improvement was noted in 70% of cases, with 20% showing no change and 10% worsening. Economic costs exceeded ₹1,000/month for 30% of patients, despite high medication adherence (80%). Conclusions: Furosemide remains the most used diuretic, but ADRs and economic burdens highlight the need for regular monitoring and cost-effective strategies. Personalized therapy can optimize outcomes, and further multicenter studies are required for broader insights.